Optimal Placement and Sizing of Capacitor in Radial Distribution System using Harmony Search Algorithm - Devabalaji K.R; Ravi K. (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Nowadays the number of consumer in the distribution system is increasing, the electricity demand and the number of capacitor bank installing is also increasing. Improper placement of capacitor bank leads to decrease the benefits of the system. In this article harmonic search algorithm is proposed to find the optimal size of the capacitor and Loss Sensitivity analysis is used to determine the location of the capacitor. In the proposed method the location for capacitor placement is chosen differently in order to minimize the power losses and Aggregative Voltage Deviation (AVD) simultaneously. The objective of this work is to minimize AVD. The proposed method is implemented on IEEE 34 bus radial distribution system and the results are compared with DE-PS and PGS method. The simulation results show the effectiveness of the proposed method.